Competitividad del sector turístico en el cantón Latacunga, provincia de Cotopaxi-Ecuador. - Gavilánez Cevallos, Vanesa Isabel (2020)
This research paper evaluates the competitiveness index of the tourism sector of Latacunga town, Cotopaxi province, Ecuador, and it determines the main factors that affect the capacity of tourist establishments in the same geographical area. For this, a sample of 50 companies was taken, using as reference the Internal Revenue Service of the active establishments for October 2019 database. By means of a questionnaire, of 50 questions with Likert scale, seven dimensions were measured that are: planning strategic, operations, quality assurance, trading, accounting and finance, human talent and environmental management. Then a mean value per dimension was calculated where all questions had the same weight. With this whole information, a simple average was made for the index of the area. Next, a plain component factor analysis was applied to establish the dimensions that affect the competitive value of the sector. As a conclusion, it was found that the competitiveness index of the tourist area of Latacunga was 0.7148, which according to the author León José Arturo is in stage III which means to have a good level of competitiveness. Following the same order, the business competitiveness index was appraised at 0.7567, placing companies in stage IV which stands for a high level of competitiveness. It should be noted that the competitiveness of companies is disadvantaged by their environment, since the cantonal competitiveness index is 0.673 and reduces the ability of companies to operate in the local market. Finally, it is assumed that it was not possible to identify a single factor that is decisive in the competitiveness of companies in the tourism sector of Latacunga town.